How Banks Go Abroad : Branches or Subsidiaries? - Cerutti, Eugenio; Dell'Ariccia, Giovanni; Martínez Pería, Maria Soledad (World Bank, Washington, DC, 2012)
The authors examine the factors that influence banks' type of organizational form when operating in foreign markets using an original database of the branches and subsidiaries in Latin America and Eastern Europe of the top 100 international banks. They find that regulation, taxation, the degree of desired penetration in the local market, and host-country economic and political risks matter. Banks are more likely to operate as branches in countries that have higher corporate taxes and when they face lower regulatory restrictions on bank entry, in general, and on foreign branches, in particular. Subsidiaries are the preferred organizational form by banks that seek to penetrate the local market establishing large and mostly retail operations. Finally, there is evidence that economic and political risks have opposite effects on the type of organizational form, suggesting that legal differences in the degree of parent bank responsibility vis-à-vis branches and subsidiaries under different risk scenarios play an important role in the kind of operations international banks maintain overseas